2005
DOI: 10.1111/j.1469-7610.2005.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal attachment state of mind moderates the impact of postnatal depression on infant attachment

Abstract: Results are discussed with reference to resiliency factors for women with postnatal depression and implications for intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
125
1
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(138 citation statements)
references
References 37 publications
8
125
1
4
Order By: Relevance
“…Maternal depression, particularly when severe and persistent, has been associated with insecure attachment between mother and infant (McMahon et al 2006). Importantly, this study further showed that women with an insecure state of mind about their own childhood attachment experiences were significantly more likely to experience both the onset of PND and recurrent episodes during early parenthood.…”
Section: Introductionsupporting
confidence: 55%
“…Maternal depression, particularly when severe and persistent, has been associated with insecure attachment between mother and infant (McMahon et al 2006). Importantly, this study further showed that women with an insecure state of mind about their own childhood attachment experiences were significantly more likely to experience both the onset of PND and recurrent episodes during early parenthood.…”
Section: Introductionsupporting
confidence: 55%
“…Por el contrario, las madres deprimidas reportan sentimientos hostiles y vivencias de estr茅s en relaci贸n al intercambio con sus beb茅s, as铆 como percepciones negativas en cuanto a las conductas que este presenta (Cornish et al, 2006). Se ha descrito una mayor incidencia de apegos infantiles inseguros en hijos/as de madres deprimidas (martins y gaffan, 2000) y se reportan m谩s efectos negativos en el v铆nculo, mientras m谩s severa y cr贸nica sea la depresi贸n de la madre (mcmahon, Barnett, Kowalenko y Tennant, 2006). Se han identificado diversos factores de riesgo para el desarrollo de depresi贸n perinatal como son la falta del apoyo social, baja autoestima y eventos de vida estresantes (matthey, Kavanagh, Howie, Barnett y Charles, 2004), pero se destaca como el mejor predictor de depresi贸n pre y post parto, la existencia de episodios depresivos previos en la madre.…”
Section: Introductionunclassified
“…The prevalence of postpartum depression is 7.6-20.9% 1,2 in China and 9.6-23% in other countries 3,4 ; it may affect appetite and sleep of puerperae and influence their recovery 5 as well as breast feeding, 6 and may cause adverse effects on the physical and psychological development of infants. 7,8 In addition, postpartum depression may also compromise the sexual desire of primiparous women, affecting quality of life of couples and conjugal relations. 9 Pharmacotherapy and psychotherapy are available for postpartum depression.…”
Section: Introductionmentioning
confidence: 99%